Manco, the Peruvian Chief : Or, An Englishman's Adventures in the Country of the Incas - Kingston, William Henry Giles, 1814-1880; Cooper, Alfred W. (Salt Lake City, UT : Project Gutenberg, 2007)
"Manco, the Peruvian Chief, An Englishman's Adventures in the Country of the Incas" by William Henry Giles Kingston is a historical novel written in the mid-19th century. The narrative centers around the protagonist, David Rexton, who, along with his English family residing in Peru, becomes embroiled in a story of adventure and danger as they help a fugitive Inca chieftain named Manco escape from Spanish authorities. The book explores themes of colonial oppression, cultural conflict, and the fight for justice, while presenting Kingston's signature depiction of perilous journeys and rugged landscapes. The opening of the novel sets the stage as David Rexton reflects on his life in Peru and the beauty of the surrounding landscape, which stands in stark contrast to the suffering of the indigenous people under Spanish rule. The family is soon confronted with the arrival of Manco, who, seeking sanctuary from his pursuers, pleads for their help. David's father ultimately decides to shelter Manco despite the potential dangers involved. This moment of compassion leads to escalating tension when Spanish officials arrive searching for the fugitive. The family's resolve to protect Manco launches a series of thrilling events filled with narrow escapes and moral dilemmas, capturing the reader's interest in both the characters' fates and the broader implications of their actions. (This is an automatically generated summary.)
Release date is 2007-05-08
Produced by Nick Hodson of London, England
Keywords: Indians of South America -- Peru -- Juvenile fiction; Peru -- Juvenile fiction